A recurrent synonymous KAT6B mutation causes Say‐Barber‐Biesecker/Young‐Simpson syndrome by inducing aberrant splicing. (3rd September 2015) - Yilmaz, Rüstem; Beleza‐Meireles, Ana; Price, Susan; Oliveira, Renata; Kubisch, Christian; Clayton‐Smith, Jill; Szakszon, Katalin; Borck, Guntram
Abstract : Mutations of the histone acetyltransferase‐encoding KAT6B gene cause the Say‐Barber‐Biesecker/Young‐Simpson (SBBYS) type of blepharophimosis‐"mental retardation" syndromes and the more severe genitopatellar syndrome. The SBBYS syndrome‐causing mutations are clustered in the large exon 18 of KAT6B and almost exclusively lead to predicted protein truncation. An atypical KAT6B mutation, a de novo synonymous variant located in exon 16 (c.3147G>A, p.(Pro1049Pro)) was previously identified in three unrelated patients. This exonic mutation was predicted in silico to cause protein truncation through aberrant splicing. Here, we report three additional unrelated children with typical SBBYS syndrome and the KAT6B c.3147G>A mutation. We show on RNA derived from patient blood that the mutation indeed induces aberrant splicing through the use of a cryptic exonic splice acceptor site created by the sequence variant. Our results thus identify the synonymous variant c.3147G>A as a splice site mutation and a mutational hot spot in SBBYS syndrome. © 2015 Wiley Periodicals, Inc.